2017
DOI: 10.1016/j.scitotenv.2017.01.147
|View full text |Cite|
|
Sign up to set email alerts
|

Groundwater arsenic contamination in Burkina Faso, West Africa: Predicting and verifying regions at risk

Abstract: Arsenic contamination in groundwater from crystalline basement rocks in West Africa has only been documented in isolated areas and presents a serious health threat in a region already facing multiple challenges related to water quality and scarcity. We present a comprehensive dataset of arsenic concentrations from drinking water wells in rural Burkina Faso (n=1498), of which 14.6% are above 10μg/L. Included in this dataset are 269 new samples from regions where no published water quality data existed. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 65 publications
0
41
0
2
Order By: Relevance
“…These meta-studies have highlighted that the majority of published studies on groundwater quality in Africa have (i) limited geographical and geological scope, (ii) studies rarely consider paired observations of microbiological and chemical water quality, and (iii) results are often reported from a mixture of different groundwater source types (e.g. Smedley 1996, Reimann et al 2003, Parker et al 2010, Sorensen et al 2015b, Bretzler et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…These meta-studies have highlighted that the majority of published studies on groundwater quality in Africa have (i) limited geographical and geological scope, (ii) studies rarely consider paired observations of microbiological and chemical water quality, and (iii) results are often reported from a mixture of different groundwater source types (e.g. Smedley 1996, Reimann et al 2003, Parker et al 2010, Sorensen et al 2015b, Bretzler et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Improved water supply which is one of the essentials for a healthy living has been constrained by uncontrolled anthropogenic activities (Vijay et al 2011;Qin et al 2013;Chen et al 2016;Chitsazan et al 2019) and by lesser extent natural conditions (Izah et al 2016;Makinde et al 2017;Zadawa and Omran 2018). Characterization of groundwater in Nigeria, is further constrained by lack of data, especially from Basement Complex areas of northern Nigeria (Akinluyi et al 2018;Olubusola et al 2018;Oyedele and Olayinka 2019;Tajudeen et al 2019), owing to difficulties associated with groundwater exploration and accessibility (Betzler et al 2017;Muhammad and Saad 2018;Oyeyemi and Aizebeokhai 2018;Ahmed and Mansor 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant progress has been made in predictive risk modeling of arsenic contamination. Several studies identified a relatively small number of geological and hydrogeochemical parameters as significant spatial proxies that can be used to predict the regional distribution of high and low arsenic concentrations across entire regions, even in areas without survey data (Amini et al, 2008;Ayotte et al, 2017;Bretzler et al, 2017;Podgorski et al, 2017;Rodriguez-Lado et al, 2013;Winkel et al, 2008Winkel et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%